Binding Modes of Doxorubicin Compared to Estratetrol and Tamoxifen - Ghozaly, Muchammad R.; Febrina, Ellin; Zaenudin, Achmad (Pharmacology and Clinical Pharmacy Research)
Doxorubicin, a compound isolated from Streptomyces peucetius var Caesius, is commonlyused in the treatment of breast cancer. This drug works by interacting on human nucleicacids. This work was aimed to study the binding modes of doxorubicin with estrogen receptoralpha (ERÎ±). Estratetrol and tamoxifen were used as natural ligand and standard drug,respectively. Molecular docking simulations was performed by AutoDock v.3.05 using minimumcoordinates -34, -6, -15 (x, y, z) and the maximum coordinates -13, 13, 3 (x, y, z).Tamoxifen formed one hydrogen bond with Glu353 (Ki=3.78 Î¼M); estratetrol binds to Glu-353, Arg394, Gly521, and His524 (Ki=0.01 Î¼M). Doxorubicin only formed one hydrogenbond with Ser317 (Ki=N/A). In conclusion, doxorubicin could not interact appropriatelywith ERÎ± due to its voluminioues structure which hinder its entrance to binding pocket ofthe macromolecule.Keywords: doxorubicin, estrogen receptor alpha.